Adjusting book budget divisions to improve advocacy: A case study of the Cape Peninsula University of Technology (CPUT). Issue 6 (5th August 2014) - Erik Moll, Michiel; Louise Patrick, Audrey; Petronella Coreejes-Brink, Anna
Abstract : Purpose: – Collection development is a key function of the university library, and is a collaborative effort. The purpose of this paper is to show how the Cape Peninsula University of Technology divides the budget between departments in such a way that it is seen as supporting key university initiatives and strategies. Design/methodology/approach: – The paper outlines the development of a formula to be used to divide the budget equitably as well as changes done. Findings: – The factors needed to develop this formula were those seen as mutually important by both parties, and even changes in university strategy could be reflected by adjusting the statistics and divisions within the formula. Research limitations/implications: – This study was restricted to only one institution. Originality/value: – The value lies in showing how what is usually seen as a purely administrative or operational tool, the book collection budget, can also be used as a tool to show support for key institutional strategies and prove library support for wider institutional changes and initiatives.